Strategic Management in Improving Madrasah Competitiveness Based on Local Excellence - Agung Bintoro; Muhammad Yusuf; Mispani Mispani (CV. Bimbingan Belajar Assyfa, 2025)
The increasingly competitive educational landscape demands that madrasahs develop distinctive advantages to maintain institutional relevance and attract community trust. However, many madrasahs in Indonesia still struggle to formulate and implement effective strategic management approaches that leverage local excellence as competitive assets. This study aims to analyze strategic management in improving madrasah competitiveness based on local excellence, focusing on strategy formulation, implementation, evaluation, as well as supporting and inhibiting factors. Using a qualitative case study approach, data were collected through in-depth interviews with madrasah heads, teachers, and community leaders, participatory observation, and documentation at a madrasah in Lampung Province. The findings reveal that strategic management is implemented through three interrelated stages: formulation involving vision-mission alignment and SWOT analysis integrated with local potential identification; implementation through flagship programs based on local excellence such as agricultural skills, religious tourism, and cultural preservation; and evaluation through continuous monitoring and stakeholder feedback. The integration of local excellence has significantly improved the madrasah's competitive advantage, reflected in increased student enrollment, strengthened community trust, and enhanced institutional reputation. Supporting factors include visionary leadership, teacher commitment, community involvement, and adequate infrastructure, while inhibiting factors include resource limitations, low digital literacy, and geographic constraints. This study concludes that local excellence-based strategic management offers a transformative approach for madrasahs to build sustainable competitiveness while preserving cultural identity and community values.